KOMODIFIKASI FEMINITAS: PERFORMANSI GENDER HOST LIVE PEREMPUAN DI TIKTOK LIVE INDONESIA - Delmarrich Bilga Ayu Permatasari; Henri Subiakto; Irfan Wahyudi (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2026)
This study examines how femininity is commodified on TikTok Live Indonesia through gender performativity, platform monetization, and local patriarchal norms. Focusing on the anonymized case of Miss W, a macro-influencer observed through more than 40 live-streaming sessions from March to May 2025, this qualitative case study combines virtual ethnographic observation and thematic content analysis. The findings show that Miss W repeatedly performs culturally legible femininity through domestic clothing, soft Javanese speech, attentive affective interaction, and participation in TikTok PK battles. These practices do not simply oppose patriarchal femininity; rather, they reconfigure ideals of modesty, gentleness, and domestic womanhood into a socially acceptable frame for sexualized visibility and virtual gift monetization. The study contributes to media and communication scholarship by linking Butlerian gender performativity with platform labor and Indonesian feminist perspectives. It argues that digital sexualization in Indonesia is not merely a global platform effect, but a culturally mediated process shaped by local gender ideologies and algorithmic reward systems.